Postoperative drainage management and wound complications following resection of lower limb soft tissue tumors: a retrospective cohort study - Gerken, Andreas; Jawny, P.; Weigl, Helene; Yang, Cui; Hardt, Julia; Menge, Franka; Hohenberger, Peter; Weiß, Christel; Reißfelder, Christoph; Jakob, Jens (Langenbeck's archives of surgery, 2023)
Postoperative wound complications are common in patients undergoing resection of lower extremity soft tissue tumors. Postoperative drainage therapy ensures adequate wound healing but may delay or complicate it. The aim of this study is to evaluate the incidence of postoperative wound complications and delayed or prolonged drainage treatment and to propose a standardized definition and severity grading of complex postoperative courses.
Gesehen am 27.06.2023